Test of 25% Ethanol Extract of Betel Nut as a Burn Wound Healing Agent in Male White Mice - Muhammad Farhan; Fathnur Sani Kasmadi; Humaryanto Humaryanto; Erni Kusdiyah; Huntari Harahap (Jurnal FARMASIMED (JFM), 2025)
Burns are a serious injury that requires effective therapy to accelerate the healing process. This study aims to evaluate the effectiveness of 25% ethanol extract of areca nut (Areca catechu L.) on healing second-degree burns in male white rats (Rattus norvegicus). The extract was obtained through a maceration method and characterized for its secondary metabolite content. A total of 25 rats were divided into five groups: a negative control (Vaseline flavum), a positive control (Bioplacenton®), and three treatment groups with extract concentrations of 2%, 4%, and 6%. The topical preparation was applied daily for 21 days, then clinical observations were carried out in the form of wound diameter measurements and histopathological analysis (re-epithelialization, collagenization, angiogenesis, and the number of fibroblasts). Phytochemical results showed that the extract contained flavonoids, alkaloids, tannins, phenols, and steroids. Clinically, the treatment group with a concentration of 6% showed the greatest reduction in wound diameter (56.6%) compared to the low concentration extract group and the negative control, although not exceeding the positive control. Histological analysis showed more even re-epithelialization, increased fibroblasts, and a more organized collagen fiber arrangement in the 6% group. These findings indicate that a 25% ethanol extract of areca nut has the potential to accelerate burn wound healing through antioxidant, antimicrobial, astringent, and anti-inflammatory mechanisms, although its effectiveness is still below standard therapy. Further research is needed to optimize the dosage and formulation for its development as an affordable, natural-based alternative phytotherapy.